Leitura do gênero propaganda e a temática da mulher negra em aula de língua portuguesa do Ensino Fundamental II - Solange Mara de Oliveira Lopes Santos (2023)
Reading of the advertising genre and the theme of the black woman in a Portuguese language class in elementary school readings aims at developing a critical reading that encourages male and female students in the final degrees of the Elementary School to discuss an Education for diversity in ethnic-racial relations. This discussion will take place from critical reading activities of advertisements that, when produced in a specific socio-historical context, use the bodies of black women to publicize some product or service. The research will be theoretically based on the Bakhtinian conception of discourse genre (2020), the statements which were produced and reproduced through concrete conditions of creation reflect the demands of the users in an established socio-historical context. Adding to the Bakhtin's theory (2020), Street (2014) and Freire (2003, 2021) they agree as theoretical references with this essay purpose by understanding that the act of reading is a social practice which happens in the interaction among subjects in different social circumstance and provokes critical awareness into students. Linked to this research, Costa (2009) and other authors that offer us the possibility of reading and understanding that involves the gender discourse of advertising as a statement that in addition to persuading the subject to buy products and services, leads to social practices that regulate or contradict rules and behaviors regarding the place and role of black women in society. To reflect and endorse this woman's social historical experience. I appropriate Gonzalez (1983) and Gomes (2022) words. The last writer takes hold of what the Black Movement brings by saying that we, black men and women, are always resistance in relation to racism, atrocities and aberrations promoted by it and as polite people, we were and are often educated in our relationship with our body and replaced by a black aesthetic and beauty. Gonzalez (1983) deepens the debate of the power relationship between the dominator (white man/colonizer) and the dominated (black woman/ex-slave) by highlighting the naturalization to which this woman was subjected regarding employment and labor market from slavery to the last decades of the twentieth century. As a summary, this project, through reading activities, in the light of these theorists, intends to teach students to read about advertisements, a discursive genre of wide media reach, how black women and their bodies were, on the one hand, according to Woodson (2022), used and publicized for many years to generate and strengthen racial prejudice in whites and self-contempt in black men and women. And, on the other hand, how these women, politicized and in a constant emancipatory process, face the social and racial inequalities caused by racism and start to occupy places and social positions previously denied them.